Desempenho agronômico e volatilização da amônia de fertilizantes pastilhados e convencionais na cultura de milho - Santos, Wadson de Menezes (2017)
Nitrogen is the most required mineral nutrient for almost all agricultural crops and the one that promotes maize yields mostly. Pastillation is a technology that allows blending urea with other mineral elements like sulfur and zinc homogeneously, aims at subsiding N losses, therefore enhancing the agronomic efficiency of the fertilizers. The aim of the first paper was to establish the recommendation of N rates and to evaluate the agronomic performance of pastille urea and its blend with sulfur and zinc, as well as commercial N sources sidedress applied to maize under the conditions of the Médio Sertão and Southern Sergipe. The experiments were carried out during the 2014 and 2015 seasons in both sites. The experimental design was Complete Blocks with 3 replications in split-plot arrangement with an additional Control treatment (TEST). In the plot 3 rates of N applications were tested: 75, 150 and 300 kg ha-1, while in the subplots the following products were evaluated: Pastille urea (UP), Pastille urea with elemental S (UP+S), Pastille urea with ammonium sulfate (UP+SA), Pastille urea with ammonium sulfate and elemental S (UP+SA+S), Pastille urea with ammonium sulfate and zinc sulfate (UP+SA+Zn), Prilled urea (UR) and Ammonium sulfate (SA). Leaf N and S contents as well as maize yield were evaluated to assess the agronomic performance of the products and to calculate the appropriate N recommendation. Economic assessments of the price for the commercial products and the corn grains allowed estimating the rate of maximum economic efficiency (DMEE). The greater the rate of N applied the higher leaf N content and grain yields of maize. Leaf S contents increased with increasing doses of S applied with the tested fertilizers. Yields with Ammonium sulfate were higher than UR, UP and UP+S in both seasons in Umbaúba (Acrisol) (Southern Sergipe). The DMEE for UR was 128 and 119 kg N ha-1 for Nossa Senhora das Dores (Acrisol) and Umbaúba, respectively. The recommended dose of SA was 119 kg ha-1, since it provided the greater incomes for both sites. In the second paper, the aim was to evaluate the agronomic performance and the losses of N through ammonia volatilization of N fertilizers sidedress applied to maize. Ammonia volatilization, leaf N content and maize yield were evaluated in all products tested in the first paper when applied at a rate of 150 kg ha-1 of N and in the TEST treatment. Three replications were used. All fertilized treatments showed higher leaf N contents and grain yields than TEST. The treatment SA showed yields higher than UP+SA+S. Of all N-NH3 lost by volatilization, 92.5% took place in the first 5 days after application. The UP+SA treatment reduced ammonia volatilization and did not differ statistically from SA and TEST. Leaf N content correlates positively and N volatilization negatively with grain yield.